2019
DOI: 10.21449/ijate.442542
|View full text |Cite
|
Sign up to set email alerts
|

Can Factor Scores be Used Instead of Total Score and Ability Estimation?

Abstract: The purpose of this study is to investigate whether factor scores can be used instead of ability estimation and total score. For this purpose, the relationships among total score, ability estimation, and factor scores were investigated. In the research, Turkish subtest data from the Transition from Primary to Secondary Education (TEOG) exam applied in April 2014 were used. Total scores in this study were calculated from the total number of correct answers given by individuals to each item. Ability estimations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Internal consistency of the variables was supported, with Cronbach’s alpha coefficient being high, between 0.859 and 0.913 (Table 5). The minimum acceptable alpha is 0.700 (Kilic, 2019), and analysis indicated that no construct had a reliability alpha less than this minimum. The construct of WP had the lowest observed alpha ( α = 0.859); thus, the study’s constructs met the reliability requirements.…”
Section: Resultsmentioning
confidence: 97%
“…Internal consistency of the variables was supported, with Cronbach’s alpha coefficient being high, between 0.859 and 0.913 (Table 5). The minimum acceptable alpha is 0.700 (Kilic, 2019), and analysis indicated that no construct had a reliability alpha less than this minimum. The construct of WP had the lowest observed alpha ( α = 0.859); thus, the study’s constructs met the reliability requirements.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to investigating relation among speaking, writing, and exposure to a language, in future studies relations with other language skills such as reading and listening comprehension in English, as well as grammar and vocabulary knowledge can be investigated. Moreover, a recent study (Kilic, 2018) shows factor scores and the total score are so related to each other that they can be used interchangeably. The factor scores give as much information as the total score about the construct the scale measures.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we used several techniques such as sum scores, above a cut-off values, standardized variables and weighted sum scores (DiStefano et al, 2009;Suhr, 2006) to compute scores for the factors. Since the various series of factor scores were highly correlated with the average scores of the scales (.211 to .867) and revealed very similar results in the statistical procedures such as Pearson's inter-correlations, hierarchical multiple regressions, and the PROCESS macro for SPSS (Model #14) that we used to test the hypotheses, we continued to use the average scores of the scales (Kilic, 2018). Thus, we measured the next three variables using the average responses to five items.…”
Section: Main Research Variablesmentioning
confidence: 99%